I−n-Coherent rings, I−n-semihereditary rings, and I-regular rings - Zhanmin, Zhu (Український математичний журнал, 2014)
Let R be a ring, let I be an ideal of R, and let n be a fixed positive integer. We define and study I−n-injective modules and I−n-flat modules. Moreover, we define and study left I−n-coherent rings, left I−n-semihereditary rings, and I-regular rings. By using the concepts of I−n-injectivity and I−n-flatness of modules, we also present some characterizations of the left I−n-coherent rings, left I−n-semihereditary rings, and I-regular rings. Нехай R — кільце, I — ідеал R, а n — фіксоване додатне цілє число. Ми визначаємо та вивчаємо I−n-ін'єктивні модулі та I−n-плоскі модулі. Крім того, визначаємо та вивчаємо ліві I−n-когерентні кільця, ліві I−n-напівспадкові кільця та I-регулярні кільця. За допомогою концепцій I−n-ін'єктивності та I−n-пологості модулів також наводимо деякі характеристики лівих I−n-когерентних кілець, лівих I−n-напівспадкових кілець та I-регулярних кілець.